TINJAUAN YURIDIS PERKAWINAN BEDA AGAMA BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 DAN HUKUM ADAT BALI - Kadek Widiantika; Ni Ketut Sari Adnyani; Dewa Bagus Sanjaya (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the legality of interfaith marriage in Indonesia and its impact in terms of Law No. 16 of 2019 and Balinese Customary Law. The type of research used is normative legal research, namely research based on statutory regulations. In this study, a statutory approach was used by examining statutory regulations related to research and a conceptual approach taking into account the views or doctrines that developed in the science of law, and a case approach based on concrete cases. . The technique for collecting legal materials in this study is using library research techniques or documentary techniques, which are collected from archive studies or literature studies such as books, papers, articles, journals, newspapers or works of experts on law. The results of this study are that there is a conflict of laws and regulations between Law No. 16 of 2019 concerning Marriage and Law No. 24 of 2013 concerning Population Administration. Then interfaith marriages have an impact on the marriage itself, have an impact on the status of children and on future inheritance.